Modern approaches to the formation of a project for the development of construction enterprises - Shaposhnikova, I.О. (Ways to Improve Construction Efficiency, 2020)
The article is devoted to the analysis of the activities of construction companies in the current economic crisis and taking into account the new requirements of society for the organization of business processes. The problems that construction enterprises are faced with today and which led to a revision of the general principles of organizing the construction business, methods of managing business processes, the formation of the organizational structure of a construction enterprise and the ethics of business communication are investigated. The priorities for the further development of enterprises in the construction industry and the main strategic steps aimed at maintaining market positions have been determined. It is noted that the emphasis of the ongoing project for the development of a construction enterprise should shift towards a quick response to the dynamics of changes. Among the many methods of effective change management, it is necessary to focus on those that will allow the company to maintain a competitive position in the market, and, if events are successful, improve them. The advantages of financial modeling of the activity of construction enterprises are analyzed. It is proposed to develop projects for the development of enterprises in the construction industry, taking into account the variability of long-term development scenarios. The necessity of conducting an economic assessment of the strategic directions of development of a construction enterprise has been substantiated. Considered are modern software products that can significantly speed up the current and forecast calculations of financial indicators of the economic activity of a construction company and effectively manage construction projects at all stages of the life cycle. Modeling of the activity of a construction company in the medium term is carried out, taking into account the goal of its further development and the current macroeconomic situation. Three scenarios of enterprise development are modeled: optimistic, realistic and pessimistic. Attention is focused on the feasibility of using software systems designed to manage construction projects, among the main capabilities of which are the choice of a strategic project, ensuring corporate project management, improving the processes and methods of construction, assessing progress in achieving goals.